Pulmonary vascular disease and exercise hemodynamics in chronic liver disease. (October 2022) - Douschan, Philipp; Kovacs, Gabor; Sassmann, Teresa; Stadlbauer, Vanessa; Avian, Alexander; Foris, Vasile; Tatscher, Elisabeth; Durchschein, Franziska; Rainer, Florian; Spindelboeck, Walter; Wagner, Martin; Kniepeiss, Daniela; et al.
Abstract: Background & aims: Portopulmonary hypertension (POPH) and hepatopulmonary syndrome (HPS) are severe pulmonary vascular complications of chronic liver disease and strongly associated with morbidity and mortality. The prevalence of these complications is relatively high in patients evaluated for liver transplantation, however it is virtually unknown in patients with stable chronic liver disease. Methods: We assessed the pulmonary hypertension (PH) and HPS prevalence in a prospective registry study of our liver out-patient clinic in a tertiary center. Between 2011 and 2016, consecutive patients with cirrhosis or non-cirrhotic portal hypertension were prospectively enrolled after written informed consent. We excluded patients with acute decompensation of liver disease and other causes of PH like severe chronic heart or lung diseases and chronic thromboembolic PH. HPS was diagnosed using contrast enhanced echocardiography and blood gas analysis. Patients were screened for PH using an algorithm implementing severity of dyspnea, echocardiography, cardiopulmonary exercise testing and exercise echocardiography employing a threshold of systolic pulmonary arterial pressure (SPAP) = 50 mmHg at peak exercise. If the algorithm indicated an increased PH risk, patients were invited for invasive investigations by means of right heart and hepatic vein catheter. We defined POPH as resting mPAP≥21 mmHg and PVR>3WU and PAWP<15 mmHg, mild PH as resting mPAP = 21–24 mmHg, and exercise PH as mPAP>30 mmHg and TPR >3 WU at peak exercise. Results: Two-hundred-five patients were enrolled (male 75%; cirrhosis 96%; median age 57 yrs). Sixty-seven patients (33%) fulfilled HPS criteria but only two (1.0%) for severe (PaO2:50–60 mmHg) or very severe HPS (PaO2<50 mmHg). In 18/77 patients (23%) undergoing exercise echocardiography, SPAP at peak exercise exceeded 50 mmHg. Finally, n = 3 (1.5%) patients were invasively diagnosed with POPH, n = 4 (2.9%) with mild PH and n = 2 with exercise PH. Conclusion: In chronic liver disease, excluding acute decompensation and other causes of PH, POPH and severe HPS are rare findings while mild to moderate HPS and mild PH or exercise PH are more frequent. Highlights: Screening for pulmonary vascular disease in patients with chronic liver disease. POPH and severe HPS are rare findings in patients with stable chronic liver disease. Exercise echocardiography revealed higher numbers of exercise PH. No association of RV dysfunction with severity of liver disease.